Dendritic structures for fluid flow: laminar, turbulent and constructal design - Miguel, A. F. (2012)
Fluid ﬂow in dendritic structures is approached based on hydrodynamics and a geometric description of the network. The hydrodynamic performance of the network, composed of series of rough ducts, is studied for both laminar turbulent ﬂow regimes. Transient response of internal ﬂuid pressure is also modelled and analyzed. The oscillatory character of the internal pressure is linked with characteristics of the ﬂuid and characteristics of the network.